Low-cost novel nano-constructed granite composites for removal of hazardous Terasil dye from wastewater - Khalil, Maria; Hanif, Muhammad Asif; Ahmad, Junaid; Alsalme, Ali; Tsubota, Toshiki (Springer Nature, 2022)
The hazardous dyes on mixing with water resources are affecting many life forms. Granite stone is popular worldwide for decorating floors, making other forms of decorative materials and items. Granite stone powder waste can be obtained free of cost from marble factories as factories spend on the disposal of this waste. In the present study, novel granite stone powder waste composite has been prepared and utilized for the effective removal of Terasil dye. Two types of granite including gray granite and white granite were used in pure, calcinized, and chemically modified forms. Freundlich adsorption isotherm model best explained the adsorption mechanism of dye removal using granite composites as compared to other adsorption isothermal models. Characterization techniques like scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy were used for the determination of morphological features and functional groups of granite composites. The obtained results were statistically analyzed using analysis of variance (ANOVA) along with the post hoc Tukey test. An extraordinarily high Terasil dye uptake capacity (more than 400 mg/g) was exhibited by granite composites prepared using sodium metasilicate. The synthesized novel nano-constructed composites provided a viable strategy as compared to the pure granite stone for dye removal from wastewater water.